Friend or patron? Social relations across the national NGO-donor divide in Ghana - Emmanuel Kumi; James G. Copestake (University of Bath, Centre for Development Studies (CDS), 2020)
The article examines the institutions governing relations between grant using national NGOs and grant giving international donors in three regions of Ghana (Upper West, Northern and Greater Accra Region). Formal procedural rules and professional norms can be viewed as necessary to minimise opportunities for informal patronage, rent-seeking and corruption made possible by the unequal access to resources. Qualitative research confirmed that friendships originating in kinship and ethnicity, school links and past collaboration can also weaken NGO sustainability. But it also highlighted the positive role informal networks, connections, personal contacts, friendship and face-to-face contact play in enhancing collaboration between donors and national NGOs, building trust and strengthening lines of accountability - with non-adherence to shared norms resulting in sanctions and reputation loss. These findings echo Eyben (2010) in affirming the positive role of informal relations, and highlighting how they can complement formal rules and professional norms governing NGO-donor relations rather than undermining them. Compared a narrow emphasis on clientelism, the research throws a more positive light on the role of informal institutions and provides a more nuanced conceptual foundation for assessing `formalisation' as a normative strategy. Donors concerned with supporting civil society need to be wary of trying to do so remotely and in ways that reduce opportunities for closer interaction and investment in trustful relationships.
Keywords: 330; Informal networks; formalisation; informal accountability; donor-NGO relationships; Ghana